2016
DOI: 10.5194/acp-16-10195-2016
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and inter-annual variability of lower stratospheric age of air spectra

Abstract: Abstract. Trace gas transport in the lower stratosphere is investigated by analysing seasonal and inter-annual variations of the age of air spectrum -the probability distribution of stratospheric transit times. Age spectra are obtained using the Chemical Lagrangian Model of the Stratosphere (CLaMS) driven by ERA-Interim winds and total diabatic heating rates, and using a time-evolving boundary-impulseresponse (BIER) method based on multiple tracer pulses. Seasonal age spectra show large deviations from an idea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
132
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(158 citation statements)
references
References 52 publications
(93 reference statements)
20
132
1
Order By: Relevance
“…This suggests that the log(TGM)-ozone relationship in the lowermost stratosphere is set in part by mixing rather than solely by chemistry (Xiao et al, 2007). The model underestimate of the log(TGM)-ozone slope could reflect excessive dynamical mixing in the lower stratosphere, a well-known problem in stratospheric transport models (Schoeberl et al, 2003;Tan et al, 2004), or errors in the timescales of air transit across the tropopause, which vary on the order of months to years (Orbe et al, 2014;Ploeger and Birner, 2016).…”
Section: Vertical Distribution and The Stratospherementioning
confidence: 99%
“…This suggests that the log(TGM)-ozone relationship in the lowermost stratosphere is set in part by mixing rather than solely by chemistry (Xiao et al, 2007). The model underestimate of the log(TGM)-ozone slope could reflect excessive dynamical mixing in the lower stratosphere, a well-known problem in stratospheric transport models (Schoeberl et al, 2003;Tan et al, 2004), or errors in the timescales of air transit across the tropopause, which vary on the order of months to years (Orbe et al, 2014;Ploeger and Birner, 2016).…”
Section: Vertical Distribution and The Stratospherementioning
confidence: 99%
“…This first moment of the arrival time distribution has a lower value than the mean age and is termed the mean arrival time. Information on the mean arrival time was derived from 2-D model calculations by Plumb et al (1999), who used the mean arrival time to detrend stratospheric correlations. They found that the detrended correlations from different years showed good agreement, if the mean arrival time was used in calculating the reference values, while this was not the case when using mean age.…”
mentioning
confidence: 99%
“…The age spectrum G used here is that for an inert tracer. As shown by Plumb et al (1999) and Ostermöller et al (2017), the arrival time distribution is better suited to describe the propagation of the organic fraction of a source gas into the stratosphere. Consequently, it is also expected that the age spectrum for an inert tracer may not be the best way to describe the propagation and release of the inorganic fraction and thus EESC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, convective uplift by typhoons has been shown to inject air masses into the outer region of the anticyclonic circulation . The interplay of these processes results in fast upward transport into the lower stratosphere and an enhanced fraction of young air in the monsoon UTLS region (Ploeger and Birner, 2016). Convection over land causes particularly fast upward transport (Tissier and Legras, 2016).…”
Section: Introductionmentioning
confidence: 99%